2008
DOI: 10.1038/nrc2460
|View full text |Cite
|
Sign up to set email alerts
|

A new MAFia in cancer

Abstract: Like JUN and FOS, the Maf transcription factors belong to the AP1 family. Besides their established role in human cancer--overexpression of the large Maf genes promotes the development of multiple myeloma--they can display tumour suppressor-like activity in specific cellular contexts, which is compatible with their physiological role in terminal differentiation. However, their oncogenic activity relies mostly on the acquisition of new biological functions relevant to cell transformation, the most striking char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
222
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(230 citation statements)
references
References 96 publications
7
222
1
Order By: Relevance
“…40,41 An interesting candidate target gene of these gains is MAFA, an oncogene with transforming properties that is overexpressed in multiple myeloma and a subtype of T-cell lymphoma. 42 We also detected recurrent gains of 8q11.1-q12.2 (harboring the LYN, MOS, and PLAG1 oncogenes) in four high-grade tumors. This is of special interest because we recently showed that gain of a 1.…”
Section: Discussionmentioning
confidence: 71%
“…40,41 An interesting candidate target gene of these gains is MAFA, an oncogene with transforming properties that is overexpressed in multiple myeloma and a subtype of T-cell lymphoma. 42 We also detected recurrent gains of 8q11.1-q12.2 (harboring the LYN, MOS, and PLAG1 oncogenes) in four high-grade tumors. This is of special interest because we recently showed that gain of a 1.…”
Section: Discussionmentioning
confidence: 71%
“…Mafb is a member of the large Maf family, which encodes leucine-zipper transcription factors (18). Mafb contributes to cell differentiation and organogenesis in a variety of cell types and tissues, including macrophages, the pancreas, and the kidney (19). The current study suggests that Mafb is required for androgen-dependent embryonic urethral masculinization.…”
mentioning
confidence: 76%
“…3 MAF is a B-ZIP transcription factor that is aberrantly expressed in myeloma by 2 distinct molecular mechanisms. 4 Approximately 10% of primary myelomas bear a MAF translocation that is associated with very high MAF expression. Typically, the MAF translocation breakpoint occurs many kilobases upstream of the MAF transcriptional start site, suggesting that the IgH enhancer elements drive transcription by regulatory elements in the normal MAF promoter.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, MAF may regulate invasion and metastasis of cancer cells through its activation of the AKT pathway. 4 These studies established MAF as a target for therapeutic intervention in MM but did not provide a ready means to achieve this clinically. In the present study, we hypothesized that MAF transcription might be driven by intracellular signal transduction pathways, downstream of MMSET, that could be inhibited by clinically available small molecules.…”
mentioning
confidence: 99%